Analysis And Design Of Information System Report Of Medical Check Up In Chio Medical Center Clinic Web-Based - Apit Priatna; Yahya Suherman; Indaryono Indaryono; Diany Anggrainy (LPPM STMIK Rosma, 2021)
Chio Medical Center is one of the services in the health sector that is engaged in special medical check-ups for prospective employees who will work and permanent employees in a company. Currently, the system that processes medical check-up report data has not been computerized properly, so that data or files are stored conventionally and it is difficult to find the required data. The research method used in this study is the System Development Life Cycle (SDLC) method and system development using the Waterfall model which starts from analysis and observation of the system running in the company. The results of the observations show that the system that runs at the Chio Medical Center clinic has not been computerized properly, namely in recording examination reports using excel and word files so that they have not been stored in a structured database. This system is designed using the Dreamweaver application as a web-based editor tool and uses the PHP and MySQL programming languages ​​as the database. The result of this research is a web-based medical check-up report information system which is expected to assist employees in inputting data and improve the process of providing information services to clients so that it is faster and more accurate.